Plant growth promoting Rhizobacteria mediated induced systemic resistance against bacterial wilt in ginger - Reshmy Vijayaraghavan (Department of Plant Pathology, College of Horticulture, 2007)
The pathogen causing bacterial wilt of ginger was isolated and identified as Ralstonia solanacearum biovar III based on its cultural, morphological and biochemical characters coupled with pathogenicity. Rhizosphere microflora of ginger from different locations of Thrissur, Waynad and Palakkad districts were isolated. Altogether, 163 rhizobacterial isolates were selected from these areas and their antagonistic activity against the pathogen assessed. Out of 163 isolates, only 45 showed antagonistic reaction. Further, study of these antagonists based on zone of inhibition resulted in selection of 20 isolates. The effect of these 20 isolates in promoting the growth of ginger was studied in pot culture in comparison with three reference cultures of P. fluorescens and B. subtilis. Result of this experiment revealed that only 11 isolates including the two reference cultures of P. fluorescens had growth promoting effect as evidenced in terms of yield and yield attributing characters of ginger. Factors which impart growth promotion in ginger by these isolates were assessed by estimating the inhibition zone, vigour index, hydrogen cyanide, indole acetic acid, ammonia production and ‘P’ solubilzation and based on that, PGPR index of the isolates was worked out. In addition to that, production of salicylic acid, antibiotics and siderphore by the isolates, the secondary metabolites which are known to play a role in disease suppression were assessed. The isolates varied in their ability to produce salicylic acid. Isolates RB-22 followed by RB-11, RB-144 and RB-66 produced more number of antibiotics which include pyoluteorin, pyrrolnitrin, 2,4DAPG etc. Similarly, isolate RB-22 and RB-11 produced maximum siderophores.